Temperament, Emotion Regulation, and Affective Family Climate in Predicting Oppositional Behaviors in Male Adolescents - parsa javanmard; Farnaz Farshbaf (دست‌آوردهای روان‌شناختی)
Aim: Background: Oppositional defiant disorder (ODD) is a condition in which children display a pattern of uncooperative, defiant, and angry behavior toward people in authority. Objectives: The present study aimed to determine the predictors of ODD among male teenagers in the city of Urmia, Iran. Methods: For this descriptive-analytical study, 384 male students between the ages of 13-16 were selected through cluster sampling. The instruments used comprised Hill Burns’ (1964) Affective Family Climate, Garnefski's Emotion Self-Regulation (2006), Cloninger’s (1994) Temperament and Character Inventory, and Achenbach’s (1991) Youth Self-Report questionnaires. Data were analyzed in SPSS v.19 using descriptive statistics, Pearson’s comparison, and regression at a significance level of p≤0.05 Results: The results showed a direct and significant correlation between emotion regulation and symptoms of ODD (0.19, p<0.01). A direct and significant relationship was also found between temperament and ODD symptoms (-0.20, p<0.01). Pearson’s correlation analyses revealed a meaningful relation between the family's emotional atmosphere and symptoms of ODD (-0.53, p<0.01). Furthermore, multiple linear regression models indicated that 39.9% of the variance of ODD is predicted by emotion regulation, family emotional atmosphere, and temperament. Conclusion: Based on the results of this study, it seems likely that ODD is influenced by emotion regulation, temperament, and affective family climate; to prevent the formation of this disorder, it is recommended that these three variables be addressed.